Konsep Pendidikan Akhlak Islam dalam Era Post-Digital: Rekonstruksi Nilai Spiritual Generasi Alfa Muslim Di Dunia Maya - Yeri Utami; Fika Amalia Putri; Tiara Mega Oktavia (TA'DIBAN, 2025)
The post-digital era has fundamentally changed the way elementary school students interact, learn, and form their self-identity, where technology is no longer merely a tool, but has become a living space integrated into their daily lives. This study aims to reconstruct the concept of Islamic moral education relevant for Alpha generation Muslim students at the elementary school level, focusing on the formation and strengthening of their spiritual values in digital spaces. Through a literature study approach that integrates the concept of Tazkiyatun nafs from classical Islamic resources with digital self-awareness theory, this research finds that moral education in the post-digital era must shift from an instructional approach to a transformative approach that emphasizes digital spiritual awareness. The study resulted in the Digital Spiritual Consciousness-Based Islamic Moral Education (PAI-DSC) model, which consists of a philosophical-theological foundation, a pedagogical-psychological framework, a digital morals curriculum, transformative learning strategies, and a supportive ecosystem. This model offers both a conceptual framework and practical guidance for PAI teachers, schools, families, and policymakers in guiding elementary school students to navigate the online world ethically, courteously, and based on Islamic values. This research provides an important contribution to developing an Islamic moral education paradigm that is adaptive, contextual, and responsive to the spiritual development dynamics of Muslim Alpha generation children in the post-digital era.